Large-scale hydrogen supply chain : a comprehensive evaluation - Incer Valverde, Jimena 1991- (Berlin, 2023)
The current climate change crisis requires extraordinary efforts to reduce the overall carbon dioxide emissions. One of the solutions to this problem is the transition of dependency from fossil fuels to renewable energy sources, such as solar, and wind. This shift to a more environmentally friendly alternative comes with many challenges. A key and suitable solution to store fluctuating renewable energy power must be established. Hydrogen is a promising energy carrier for storing and distributing renewable energy around the world. This thesis provides a comprehensive analysis of the large-scale hydrogen economy. It extensively evaluates the entire process of green liquid hydrogen, including gas and liquid hydrogen production, as well as the reconversion to hydrogen gas via the regasification of liquid hydrogen. The study includes energetic, exergetic, and economic analyses. For green hydrogen production, a PEM electrolyzer is considered, and an exergy efficiency of 60% is calculated, and the levelized cost of green hydrogen amounts to 8.8 US$/kgH2. For the liquefaction of hydrogen, the exergetic efficiency is determined to be 42%, and the levelized cost of liquid hydrogen corresponds to 1.7 US$/kgH2. For hydrogen regasification, the exergy efficiency is found to be 62%. A levelized cost for hydrogen regasification is calculated at 0.7 US$/kgH2. Additionally, the costs are determined based on different operating hours and electricity prices. For the values above, 7446 h/a and 110 US$/MWh were considered, respectively. Even though large-scale hydrogen regasification presents challenges due to the cryogenic temperature of liquid hydrogen (-252.8 °C), it also offers the potential to use the transferred exergy during the regasification process, which would otherwise be destroyed. Hydrogen is the smallest element in the periodic table, and it presents many challenges in its pure form due to its reactivity. Therefore, four pathways for hydrogen...
Tesis (doctorado en ingeniería química)--Universidad Técnica de Berlín. Facultad de Ciencias, 2023
Se considera un trabajo Final de Graduación del Sistema de Estudios de Posgrado, según oficio no. OAICE-745-2025
Keywords: HIDRÓGENO LÍQUIDO; HIDRÓGENO -- INDUSTRIA Y COMERCIO; RECURSOS ENERGETICOS RENOVABLES